Application of chitosan coating on alginate beads for cryopreservation uses - Schneider Teixeira, Aline (2014)
Calcium alginate gel beads readily interchange solutes with the bulk solution and water with the surrounding media. The transfer properties are often critical for its use, either for its stability and preservation or textural modulation, or for the convenient treatment of contained tissues for cryopreservation. Chitosan has been evaluated for various uses in food, medical, pharmaceutical, agricultural and chemical industries because of its non-toxic, biocompatible, mucoadhesive, and biodegradable properties. A new approach for chitosan application is analyzed: to both protect against microbial-derived damages and to consider permeability modulation on alginate gel beads employed in cryopreservation. Characterization of combined systems of calcium alginate with chitosan coating should be addressed before including the germplasm tissue. The effect of polysaccharide composition was evaluated on dehydration kinetics. Frozen and unfrozen water fractions for beads with and without chitosan coating were determined by DSC and thermodynamic parameters were calculated. Microstructure was evaluated by SEM, cryo-SEM and FTIR. Results obtained suggest a promising utility of these polysaccharides combination for cryopreservation protocol.